Investigation of continuous human weight monitoring based on optical fiber sensor - Nas ‘Adilah, Mohd Adif (2022)
Measuring weight help to show the growth process for health monitoring. It is crucial to get an accurate value to determine the actual weight of human without any external load. The aim of measuring human weight is to access and monitor fluid nutrition status and monitor the effectiveness of nutritional support for the ideal body weight. There are many existing sensors type in market place used for determine the weight. However, it have many external factors interfering with the accuracy and the cost. Sometimes, it require the huge size to perform the accuracy and high cost. Currently, most of sensors are not water resistance which can affected the weighing system.the aim of this study is to study and develop a potentially low cost weightage sensor based on optical sensor using intensity modulation technique and the effect of different weight load on the optical fiber gap between the input and output fibers. An incident beam will travel between two optical fibers with a 2mm gap and it will be detected by photodetector and produce an output voltage. Data were collected from the several subject with different load. The measured value will slightly difference from the real value using the accuracy formula to obtain the lowest value of error when experiment is run. Two optical fiber are placed in parallel with each other, where light source and photodetectors are placed at respective ends of optical fiber. A type of cylinder with measurand is used as a tank or reservoir for sample, where a hole is made at each side fitting the fiber. Intensity-modulation proves to be an easy method to analyse as the output of the system is in voltage. Variation in output voltage signals the changes of light intensity at the receiving fiber undergone through the measurand. System can detect changes in load applied. In the future, sensor measurements for this method would be used to develop an advanced monitoring system where it is fully autonomous reducing the manpower needed.